IMPLEMENTASI E-MODUL IPA SEKOLAH DASAR BERBASIS BRAIN BASED LEARNING - Muslim, Yudi Aziz; Nuryani, Lilis Kholisoh; Rahman, Abdul; Sumiati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of information technology has driven the need for innovation in science learning in elementary schools, one of which is through the use of digital-based e-modules. This study aims to examine the implementation of Brain-Based Learning (BBL)-based science e-modules in improving learning quality. The method used was a literature review, analyzing various relevant scientific sources through the stages of identification, selection, content analysis, and data synthesis. The study results indicate that digital-based e-modules can improve learning independence, conceptual understanding, and student engagement in learning. The integration of the BBL approach has been proven to create more meaningful, enjoyable, and brain-friendly learning, thus positively impacting students' critical thinking skills. Furthermore, the effectiveness of e-modules is maximized when combined with innovative learning models such as Problem-Based Learning, STEM, and Research-Based Learning. However, the implementation of BBL-based e-modules still faces challenges, such as limited technological facilities and teacher preparedness. Therefore, systematic development through a Design-Based Research approach, along with adequate training and infrastructure support, is needed. Therefore, BBL-based science e-modules have great potential as an innovative solution to improve the quality of science learning in elementary schools.